Baccharis trimera (Less.) DC: An Innovative Cardioprotective Herbal Medicine Against Multiple Risk Factors for Cardiovascular Disease - Souza, Marília Moraes Queiroz; Silva, Gustavo Ratti Da; Cola, Itaruã Machri; Silva, Aniely Oliveira; Schaedler, Maysa Isernhagen; Guarnier, Lucas Pires; Palozi, Rhanany Alan Calloi; Barboza, Lorena Neris; Menetrier, Jacqueline Vergutz; Froelich, Diego Lacir; Auth, Pablo Alvarez; Veiga, Alan De Almeida; et al. (SAGE Publications, 2020)
Cardiovascular disease (CVD) is the leading cause of death worldwide and among its modifiable risk factors are dyslipidemia, diabetes, and smoking. Experimental models evaluated this risk factors singly, however, there is a lack of models that agglomerate these risk factors, resembling real patients and elucidating the pathophysiology of CVD. Moreover, few studies have investigated the cardioprotective effects of Baccharis trimera, a species with lipid-lowering effects. In this study, ethanol-soluble fraction of B. trimera was characterized by liquid chromatography-mass spectrometry. Diabetes was induced by streptozotocin in Wistar rats that also received 0.5% cholesterol-enriched chow and were exposed to the smoke of nine cigarettes, 5 days/week, for 4 weeks. During the last 2 weeks, the animals were treated with vehicle (C-), B. trimera, or simvastatin plus insulin. At the end, cholesterol, triglyceride, urea, and creatinine levels; blood pressure (BP); heart rate (HR); abdominal aortic morphometry; vascular reactivity; renal and cardiac oxidative status; and histopathological changes were evaluated. The agglomerate of risk factors promoted alterations contrary to those described in the literature for the isolated risk factors. The C- group exhibited oxidative stress, increase in biochemical parameters, and thickening of the wall of the abdominal aorta. HR, systolic, diastolic, and mean BP decreased, and vascular reactivity was altered. Cardiac and renal histopathological changes were observed. Treatment with B. trimera reversed these changes and this effect may be partially attributable to lipid-lowering action and to the inhibition of free radical generation. B. trimera has cardioprotective effects in this model, with no toxicity.
Keywords: carqueja; diabetes mellitus; dyslipidemia; herbal medicine; rats; smoking